2022
DOI: 10.30813/jab.v15i1.2796
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Perbandingan Abnormal Return Dan Trading Volume Activity Sebelum Dan Sesudah Diumumkannya Kasus Pertama Covid-19

Abstract: <p><strong><em>ABSTRACT: </em></strong><em>The purpose of this study was to examine the information content of the announcement of the first Covid-19 case in Indonesia by looking at the differences in Abnormal Return and Trading Volume Activity both before and after the event. The method used in this research is an event study. The research period used was 6 stock exchange days, namely 3 days before and 3 days after the announcement of the first Covid-19 case in Indonesia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
1
0
5
Order By: Relevance
“…The results of this study align with the research of Fadhilah et al (2021), which found no differences in trading volume before and after the announcement of the arrival of the Sinovac vaccine in Indonesia. As for other studies that obtained the same results, namely the research of Sahputra et al (2022), which found no differences in trading volume before and after the announcement of the first case of COVID-19 in Indonesia.…”
Section: Differences In the Level Of Trading Volume Activity Before A...supporting
confidence: 79%
See 1 more Smart Citation
“…The results of this study align with the research of Fadhilah et al (2021), which found no differences in trading volume before and after the announcement of the arrival of the Sinovac vaccine in Indonesia. As for other studies that obtained the same results, namely the research of Sahputra et al (2022), which found no differences in trading volume before and after the announcement of the first case of COVID-19 in Indonesia.…”
Section: Differences In the Level Of Trading Volume Activity Before A...supporting
confidence: 79%
“…Research by Ibrahim et al (2022) shows differences in abnormal returns and trading volume before and after the COVID-19 vaccination in healthcare and banking sector companies. Sahputra et al (2022) disclose differences in abnormal returns before and after the announcement of the first case of COVID-19 in Indonesia, and there was no difference in trading volume before and after the announcement of the first case of COVID-19 in Indonesia. Therefore, this research was conducted to re-examine the reaction of the Indonesian capital market to non-economic events.…”
Section: Introductionmentioning
confidence: 84%
“…Pasar yang efisien berdasar pada edisiensi informasi yakni seberapa cepat respon pasar terhadap suatu berita yang menjadi informasi bagi investor hingga akan mempengaruhi aktivitas perubahan harga pasar sekuritas menuju pada keseimbangan harga baru (Sihombing & Sukmadilaga, 2018). Sehingga dapat disimpulkan anggapan dasar pada pasar efisien, harga saham sensitif terhadap informasi disekelilingnya, perubahan harga saham signifikan dengan intensitas informasi seputar harga saham yang menggambarkan perubahan informasi disekitarnya, selanjutnya informasi tersebut akan digunakan oleh investor sebagai indikator untuk proyeksi harga saham di masa mendatang (Sahputra et al, 2022).…”
Section: Tinjauan Pustakaunclassified
“…Jika suatu peristiwa menyebabkan timbulnya abnormal return, maka hal tersebut jelas mendapat rekasi dari pasar, pasar menganggap peristiwa yang terjadi tersebut bersifat informatif. Hasil studi terdahulu menunjukkan terdapat abnormal return yang dikaji oleh (Alam et al, 2020) (Herwany et al, 2021) (Carter et al, 2022) (Suharti & Saftiana, 2021) (Sahputra et al, 2022) (Kusumayanti & Suarjaya, 2018) (Wicaksono & Adyaksana, 2020). Sedangkan penelitian (Pradnyani & Sisdyani, 2015) (Sambuari et al, 2020)(Olivia Sirait, 2023 membuktikan jika tidak terdapat perbedaan antara abnormal return sebelum dan sesudah peristiwa non-ekonomi.…”
Section: Tinjauan Pustakaunclassified
See 1 more Smart Citation